Molecular Epidemiology of Enterovirus 71 Infection in the Central Region of Taiwan from 2002 to 2012 - Wu, Wen-Hao (Public Library of Science, 2013)
Enterovirus 71 (EV71), a causative agent of hand, foot, and mouth disease can be classified into three genotypes and many subtypes. The objectives of this study were to conduct a molecular epidemiological study of EV71 in the central region of Taiwan from 2002–2012 and to test the hypothesis that whether the alternative appearance of different EV71 subtypes in Taiwan is due to transmission from neighboring countries or from re-emergence of pre-existing local strains. We selected 174 EV71 isolates and used reverse transcription-polymerase chain reaction to amplify their VP1 region for DNA sequencing. Phylogenetic analyses were conducted using Neighbor-Joining, Maximum Likelihood and Bayesian methods. We found that the major subtypes of EV71 in Taiwan were B4 for 2002 epidemic, C4 for 2004–2005 epidemic, B5 for 2008–2009 epidemic, C4 for 2010 epidemic and B5 for 2011–2012 epidemic. Phylogenetic analysis demonstrated that the 2002 and 2008 epidemics were associated with EV71 from Malaysia and Singapore; while both 2010 and 2011–2012 epidemics originated from different regions of mainland China including Shanghai, Henan, Xiamen and Gong-Dong. Furthermore, minor strains have been identified in each epidemic and some of them were correlated with the subsequent outbreaks. Therefore, the EV71 infection in Taiwan may originate from pre-existing minor strains or from other regions in Asia including mainland China. In addition, 101 EV71 isolates were selected for the detection of new recombinant strains using the nucleotide sequences spanning the VP1-2A-2B region. No new recombinant strain was found. Analysis of clinical manifestations showed that patients infected with C4 had significantly higher rates of pharyngeal vesicles or ulcers than patients infected with B5. This is the first study demonstrating that different EV 71 genotypes may have different clinical manifestations and the association of EV71 infections between Taiwan and mainland China.